Integrasi Pendidikan Lingkungan dan Kearifan Lokal dalam Era Society 5.0 untuk Menumbuhkan Kesadaran Global dan Cinta Budaya pada Siswa Sekolah Dasar - Salsabela, Wesi; Putri, Miranda Ade Tias; Noviyanti, Silvina (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
This article explores the integration of environmental education and local wisdom into elementary school learning to foster global awareness and cultural appreciation from an early age, particularly within the context of digital advancement in the Society 5.0 era. The study employs a qualitative analytical method with a conceptual approach, based on scientific articles published over the past ten years (2015-2025). Data analysis was conducted through data selection, thematic categorization, and descriptive-qualitative interpretation to examine the relationship between theory and real educational practices in the context of elementary education in Society 5.0. The findings indicate that environmental education and local wisdom play a significant role in shaping students' character at the primary level, especially amid rapid technological development. These values can be effectively integrated through thematic-contextual learning approaches aligned with students’ developmental stages and curriculum content. Teachers hold a strategic role in designing and implementing meaningful learning, serving as facilitators, character builders, and instructional innovators. The article concludes that integrating environmental and cultural values into elementary school learning is a relevant strategy to cultivate global consciousness and cultural identity from an early age.Keywords - Environmental Education, Local Wisdom, Elementary School, Society 5.0, Global and Cultural Awareness.